Kurdish Community Differences: Potential Conflict and Politics in The Middle East - Setiawan, Refly; Vladimirov Mladenov , Stanislav; Soydan, Mustafa Zafer; Melinda, Esti (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2023)
The Kurds are the name of an ethnic group that occupies several countries in the Middle East, notably Iraq, Iran, Türkiye, and a small part of Syria. The existence of Kurds who are different from ethnic groups in general has always been seen as a regional problem and treated discriminatorily. Because of this, the Kurds always carry out movements, even rebellions, to fight for political rights. The method used in this research is qualitative research with a library approach. The results of the study show that each Kurdish community spread across each country has differences that are not too prominent. In general, the difference lies in the direction of their movement based on the group leader and the religion they adhere to. Although the majority of Kurds adhere to Sunni Islam, there are also those who practice different religions, such as Christianity, Judaism, Yazidis, and Zoroastrians. Currently, there are still many people who think that the Kurds are a tribe that always causes problems, although there are also those who think that most Kurds want recognition for their existence and special autonomy for the area where they live.